2020
DOI: 10.1007/s11664-019-07920-1
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Graphene Electronics by Inkjet Printing

Abstract: Graphene is currently emerging as an alternative to traditional conductive materials, such as copper and silver because of its excellent electrical conductivity and earth's carbon abundance. Graphene can be applied in many different electronic fields with different manufacturing methods to meet their specific requirements, which promote the development of advanced manufacturing technology in graphene electrical applications. Inkjet printing, as an environmentally friendly, low-cost and simple-to-operate advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 141 publications
(141 reference statements)
0
14
0
Order By: Relevance
“…At present, many researchers have done a lot of research works on the preparation of inkjet printing inks and the printing of functional circuits [ 23 , 24 , 25 , 26 ]. However, they mainly focused on nanoparticles (silver nanoparticles, graphene) [ 27 , 28 ] or organic materials (solution-processed poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT: PSS), polyaniline) [ 29 ] as conductive fillers. Recently, the inkjet-printed non-spherical noble metal nanoparticles patterns useful for drug release were reported by Chirico and coworkers [ 30 , 31 ], which indicated that the inkjet printing technology has a wider range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many researchers have done a lot of research works on the preparation of inkjet printing inks and the printing of functional circuits [ 23 , 24 , 25 , 26 ]. However, they mainly focused on nanoparticles (silver nanoparticles, graphene) [ 27 , 28 ] or organic materials (solution-processed poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT: PSS), polyaniline) [ 29 ] as conductive fillers. Recently, the inkjet-printed non-spherical noble metal nanoparticles patterns useful for drug release were reported by Chirico and coworkers [ 30 , 31 ], which indicated that the inkjet printing technology has a wider range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Coalescence is an enticing phenomenon for study by the fluid dynamicist as it involves several of the major force contributions seen in the field namely capillary, viscous, inertial and gravity forces. The study of coalescing fluids has allowed for advances in microfluidics (Prakash & Gershenfeld 2007), additive manufacturing in microgravity (Huang et al 2020), bioprinting of living tissue (Murphy & Atala 2014), the inkjet printing of electronics (Zhu, Wang & Zhu 2020) and even the study of natural phenomena such as rain (D'Adderio, PorcĂč & Tokay 2018). Coalescence can largely be separated into drop-drop coalescence (Yuan et al 2015;Duchemin, Eggers & Josserand 2003;Gebauer et al 2016), bubble coalescence (Liu et al 2019;Cui et al 2016;Feng et al 2016;Han et al 2016), the study of onset (Neitzel & Dell'Aversana 2002;Geri et al 2017) and drop-planar coalescence (Politova et al 2017;Zhang et al 2019;Kirar et al 2020) which is the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…The study of coalescing fluids has allowed for advances in microfluidics (Prakash & Gershenfeld 2007), additive manufacturing in microgravity (Huang et al. 2020), bioprinting of living tissue (Murphy & Atala 2014), the inkjet printing of electronics (Zhu, Wang & Zhu 2020) and even the study of natural phenomena such as rain (D'Adderio, PorcĂč & Tokay 2018). Coalescence can largely be separated into drop–drop coalescence (Yuan et al.…”
Section: Introductionmentioning
confidence: 99%
“…With the emergence of modern printing electronic technology, the printing electronic industry based on nano-silver conductive ink is developing rapidly (Murtaza et al , 2020; Reenaers et al , 2020; Mo et al , 2016; Zhao et al , 2020). The application of nano-silver ink in the electronic industry mainly includes intaglio printing (Pudas et al , 2005; Sico et al , 2016; Huang and Zhu, 2018), flexographic printing (Kattumenu et al , 2009), screen printing (Wang et al , 2014; Faddoul et al , 2011), inkjet printing (Liu et al , 2019; Zhu et al , 2020; Huang et al , 2011; Li et al , 2014; Perelaer et al , 2009; Zhang et al , 2011; Woo et al , 2009) and three-dimensional (3 D) printing (Kim et al , 2006; Mu et al , 2018; Ghosale et al , 2016). In the gravure printing, flexographic printing and screen printing processes, the printed circuit board manufacturing process requires many steps.…”
Section: Research Background and Significancementioning
confidence: 99%